Drug-loaded bubbles with matched focused ultrasound excitation for concurrent blood–brain barrier opening and brain-tumor drug delivery. (15th March 2015) - Fan, Ching-Hsiang; Ting, Chien-Yu; Chang, Yuan-Chih; Wei, Kuo-Chen; Liu, Hao-Li; Yeh, Chih-Kuang
Graphical abstract: Abstract: Focused ultrasound (FUS) with microbubbles has been used to achieve local blood–brain barrier opening (BBB opening) and increase the penetration of therapeutic drugs into brain tumors. However, inertial cavitation of microbubbles during FUS-induced BBB opening causes intracerebral hemorrhaging (ICH), leading to acute and chronic brain injury and limiting the efficiency of drug delivery. Here we investigated whether induction of drug (1, 3-bis(2-chloroethyl)-1-nitrosourea, BCNU)-loaded bubbles (BCNU bubbles) to oscillate at their resonant frequency would reduce inertial cavitation during BBB opening, thereby eliminating ICH and enhancing drug delivery in a rat brain model. FUS was tested at 1 and 10 MHz, over a wide range of pressure (mechanical index ranging from 0.16 to 1.42) in the presence of BCNU bubbles. Excitation of BCNU bubbles by resonance frequency-matched FUS (10 MHz) resulted in predominantly stable cavitation and significantly reduced the occurrence of potential hazards of exposure to biological tissues during the BBB opening process. In addition, the drug release process could be monitored by acoustic emission obtained from ultrasound imaging. In tumor-bearing animals, BCNU bubbles with FUS showed significant control of tumor progression and improved maximum survival from 26 to 35 days. This study provides useful advancements toward the goal of successfully translating FUS theranostic bubble-enhanced brain drug delivery into clinical use.